The experiences of caregivers for older persons among the Chinese in urban Kuching, Sarawak - Chung, Raymond Chiun Han (Universiti Malaysia Sarawak (UNIMAS), 2012)
In most parts of the world, people have in recent years been living longer lives. There are various reasons for this, including advancements in medical science and better living standards brought about by rising wealth and development of nation9 While this is invariably seen as a positive development, and life expectancy at birth is often used as a yardstick to measure a country's level of development, it nevertheless also has a downside. As people grow older, many will also become frail especially in later years. They will require aged-care facilities and end-of-life care, which may be provided in their own homes or in special purpose-built facilities including retirement homes, nursing homes and hospices. Some will require caregiving, which refers to the process in which one or more persons assist them to carry out activities of daily life (ADLs) such as getting out of bed, moving around the home, washing and changing, eating and so on. Sometimes, the assistance may extend to helping with activities such as shopping, financial transactions and similar miscellaneous errands. A major stakeholder in caregiving for the elderly frail is a member of the famHy. This could be a spouse, children, children-in-Iaw, sibling or some other closely related member of the care recipient's family.